Effect of computer game playing on baseline laparoscopic simulator skills. - Halvorsen, Fredrik H; Cvancarova, Milada; Fosse, Erik; Mjåland, Odd (Surgical Laparoscopy, Endoscopy & Percutaneous Techniques, 2013)
BACKGROUND: Studies examining the possible association between computer game playing and laparoscopic performance in general have yielded conflicting results and neither has a relationship between computer game playing and baseline performance on laparoscopic simulators been established. OBJECTIVE: The aim of this study was to examine the possible association between previous and present computer game playing and baseline performance on a virtual reality laparoscopic performance in a sample of potential future medical students. DESIGN: The participating students completed a questionnaire covering the weekly amount and type of computer game playing activity during the previous year and 3 years ago. They then performed 2 repetitions of 2 tasks ('gallbladder dissection' and 'traverse tube') on a virtual reality laparoscopic simulator. Performance on the simulator were then analyzed for association to their computer game experience. SETTING: Local high school, Norway. PARTICIPANTS: Forty-eight students from 2 high school classes volunteered to participate in the study. RESULTS: No association between prior and present computer game playing and baseline performance was found. The results were similar both for prior and present action game playing and prior and present computer game playing in general. CONCLUSION: Our results indicate that prior and present computer game playing may not affect baseline performance in a virtual reality simulator.